Oversized self-expanding stents as an alternative to flow-diverters for blister-like aneurysms. (April 2014) - Grant, Ryan A.; Quon, Jennifer L.; Bulsara, Ketan R.
<x content-type="archive" xml:space="preserve">Abstract</x> Objective: Blister-like aneurysms (BLAs) are challenging to treat. Their friable nature makes them high risk for both traditional microsurgical and endovascular treatments. We discuss employing a single oversized self-expanding stent in the treatment of these treacherous lesions. Methods: A retrospective review from our institution was conducted. Five patients with BLAs were identified, who went on to be treated with a single oversized self-expanding stent, defined as 1 mm larger than the parent vessel, by the senior author (KRB), who is dual fellowship trained in both cerebrovascular/skull base microsurgery and endovascular neurosurgery. Additionally, a literature review was performed on BLAs treated with sole stenting and outcomes discussed. Results: Our five patients had complete aneurysm occlusion at long-term follow-up and all had good neurological outcomes. The literature review demonstrated that most aneurysms at long-term follow-up were either completed occluded or progressively becoming occluded, with patients overall having a good functional outcome based on the modified Rankin scale (mRS). Conclusion: In our experience, oversized self-expanding stents are a treatment option that should be considered for BLAs. This strategy avoids the need for dual antiplatelet therapy and therefore increases its utility in the case of subarachnoid hemorrhage (SAH).